Targeting MutT Homolog 1 (MTH1) for Breast Cancer Suppression by Using a Novel MTH1 Inhibitor MA−24 with Tumor-Selective Toxicity - Nannan Kang; Jun Ma; Yuling Hu; Rongrong Di; Lei Wang; Xuanling Zhang; Yisheng Lai; Yu Liu (Pharmaceuticals, 2024)
Background: Breast cancer is a commonly diagnosed cancer worldwide. Human MutT homolog 1 (MTH1) is found to be elevated in breast tumors and cancer cells need MTH1 for survival. Pharmacological inhibition of MTH1 may be potentially beneficial in the treatment of breast cancer. Methods: MA−24 was screened by malachite green colorimetric assay for MTH1 inhibitors and the kinetic characteristics of MA−24 were assessed. The features of MA−24’s binding with MTH1 were ascertained through molecular docking, and the cytotoxic activity of MA−24 was validated in vitro and in vivo. Target engagement assays, comet assay, and Western blot confirmed the intracellular target and mechanism of MA−24. Results: MA−24 shows potent antitumor bioactivity both in vitro and in vivo. MA−24 competitively inhibited the MTH1 and further induced DNA strand breaks, leading to increased apoptosis of cancer cells depending on the upregulation of the cleaved-caspase 3–cleaved-PARP axis. In particular, MA−24 exhibited a powerful efficacy and safety in vivo (tumor growth inhibition rate: 61.8%). Conclusions: MA−24 possesses a broad spectrum of breast cancer cytotoxicity and offered valuable insights for overcoming the challenges of chemotherapy-related toxicity, which holds great potential for the further development MA−24 as an anti-cancer drug.